The Large Right Heart Is Associated with the Prolongation of the Procedure Time of Leadless Pacemaker Implantation - Kataoka, Naoya (Medicina (Kaunas), 2021)
Background and objectives: Leadless pacemakers are less invasive but are as effective as conventional pacemakers and are increasingly implanted in elderly patients. However, the implantation procedure is sometimes challenging in patients with abnormal anatomy, particularly those with an enlarged right heart. We aimed to determine the right heart parameters that were associated with longer procedure times for leadless pacemaker implantation. Materials and Methods: Among 19 consecutive patients in whom Micra leadless pacemakers (Micra TPS, Medtronic, Minneapolis, MN) were implanted, the diameter and area of both the right atrium and right ventricle were measured by transthoracic echocardiography before the procedure. The right heart parameters that were associated with a procedure time > 60 min were investigated. Results: In the 19 patients (median 81 years old, 10 male) who underwent implantation of the Micra system, 6 (32%) required a procedure time > 60 min. Among the baseline right heart echocardiographic parameters, right atrial diameter and area were significantly associated with a procedure time > 60 min (odds ratio 11.3, 95% confidence interval 1.09–1.17, p = 0.042; and odds ratio 1.57, 95% confidence interval 1.05–2.34, p = 0.029, respectively) at a cutoff of 4.0 cm and 17.0 cm(2), respectively. Conclusions: Patients with an enlarged right atrium may not be good candidates for leadless pacemakers given the longer procedure time, and conventional pacemakers should perhaps be recommended as an alternative.